The Effectiveness of Using The Goat’s Secret; Illustrated English Short Stories to Improve Grammar Ability of The Second Grade of SMPN 20 Purworejo in The Academic Year of 2015/2016 - Fuad Syaifudin (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2019)
This study is aimed to describe whether or not there is any the effectiveness of using The Goat’s Secret; illustrated English short stories to improve grammar ability of the second grade of SMPN 20 Purworejo n the academic year of 2015/2016. In order to master English well, the elements of the language such as vocabulary, grammar, and sound system must also be taught to the students as the basic knowledge to words the English use and skill. Through the study of grammar, students would become more familiar with the grammar of their native language and that this familiarity would help them understand, so they can speak and write better. The result of the research revealed that the mean score of control group is 76.27 fell in good category. The mean score of experimental group is 81.93 fell in excellent category. Besides, to know whether Ha is accepted or rejected the researcher consulted to the t-test. The t-value was consulted to the t-table at the 5% significance level. It shows that t table is 2.000 and the t value is 14.275. It means that t value is higher than t table. Therefore, it can be concluded that the use of illustrated English short stories in improving students’ grammar ability at the second grade students of SMPN 20 Purworejo in the academic year of 2015/2016 is effective.